2014
DOI: 10.5194/acp-14-12251-2014
|View full text |Cite
|
Sign up to set email alerts
|

Relations between erythemal UV dose, global solar radiation, total ozone column and aerosol optical depth at Uccle, Belgium

Abstract: Abstract. At Uccle, Belgium, a long time series of simultaneous measurements of erythemal ultraviolet (UV) dose (S ery ), global solar radiation (S g ), total ozone column (Q O 3 ) and aerosol optical depth (τ aer ) (at 320.1 nm) is available, which allows for an extensive study of the changes in the variables over time. Linear trends were determined for the different monthly anomalies time series. S ery , S g and Q O 3 all increase by respectively 7, 4 and 3 % per decade. τ aer shows an insignificant negativ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
56
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(64 citation statements)
references
References 82 publications
7
56
1
Order By: Relevance
“…3d) was only affecting the EUV radiation doses in winter months; therefore, its effect throughout the decades was the weakest of all the studied variables (r part ranging from 0.16 in the decade 1984-1993 to 0.25 in the decade 2004-2013). The results concur with similar studies performed at other European locations, showing that TOC is the main driver of long-term EUV radiation changes, while SZA and cloud cover are the dominant factors affecting EUV radiation in the short term (Den Outer et al, 2010;Herman, 2010;De Bock et al, 2014). The changes in EUV radiation in the 1970s have been attributed to cloud cover variability, which is in accord with the high r part shown in Fig.…”
Section: Factors Affecting the Erythemal Uv Radiation Dosessupporting
confidence: 82%
See 1 more Smart Citation
“…3d) was only affecting the EUV radiation doses in winter months; therefore, its effect throughout the decades was the weakest of all the studied variables (r part ranging from 0.16 in the decade 1984-1993 to 0.25 in the decade 2004-2013). The results concur with similar studies performed at other European locations, showing that TOC is the main driver of long-term EUV radiation changes, while SZA and cloud cover are the dominant factors affecting EUV radiation in the short term (Den Outer et al, 2010;Herman, 2010;De Bock et al, 2014). The changes in EUV radiation in the 1970s have been attributed to cloud cover variability, which is in accord with the high r part shown in Fig.…”
Section: Factors Affecting the Erythemal Uv Radiation Dosessupporting
confidence: 82%
“…According to numerous studies, atmospheric circulation and stratospheric temperature greatly affect the intensity of global ozone losses (e.g., Orsolini and Limpasuvan, 2001;Schnadt and Dameris, 2003;Hofmann et al, 2009). In the 1970s-1990s, TOC trends in central Europe showed a decline by about 3-4 % per decade, especially in spring, while the recovery of the ozone layer has been reported since the end of the 1990s (e.g., Krzyścin et al, 1998;Krzyscin and Borkowski, 2008;Vaníček et al, 2012;De Bock et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Signs from the onset of ozone recovery since the late 1990s on surface UV-B irradiance have been mainly detected over the northern high latitudes; recent studies indicate that UV-B has been declining during the last 2 decades (Bernhard, 2011;Eleftheratos et al, 2014). However, during the same period, both the UV-B and the UV-A irradiance are increasing over many locations in the Northern Hemisphere mid-latitudes, mainly due to the negative trends in the amount of clouds and aerosols (De Bock et al, 2014;Fitzka et al, 2012;Román et al, 2015;Smedley et al, 2012;Zerefos et al, 2012). In a recent study, Fragkos et al (2015) showed that in Thessaloniki, even under extreme high (low) total ozone column (TOC) conditions, the erythemal irradiance can be lower (higher) than its climatological values due to the dominant effect of aerosols.…”
Section: Fountoulakis Et Al: Short-and Long-term Variability Of Smentioning
confidence: 98%
“…Upward UVB and UVA trends have been reported over several mid-latitudinal sites of the Northern Hemisphere since the beginning of the 1990s, which have been mainly attributed to decreasing attenuation by aerosols and clouds (e.g. Krzyścin et al, 2011;Zerefos et al, 2012;De Bock et al, 2014).…”
Section: Introductionmentioning
confidence: 99%